2005
DOI: 10.1128/jvi.79.16.10821-10825.2005
|View full text |Cite
|
Sign up to set email alerts
|

Studies of H5N1 Influenza Virus Infection of Pigs by Using Viruses Isolated in Vietnam and Thailand in 2004

Abstract: To determine whether avian H5N1 influenza viruses associated with human infections in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
144
1
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(159 citation statements)
references
References 12 publications
9
144
1
5
Order By: Relevance
“…However, an exaggerated inflammatory response is believed to contribute to H5N1-associated morbidity and mortality [52][53][54][55]. For example, the resistance of pigs to severe H5N1-mediated disease correlated with the lack of a strong pro-inflammatory response following infection [56][57][58]. Combined with evidence that macrophages support productive replication of some IAV strains, excessive cytokine production following H5N1 infection may be a result of productive virus replication in macrophages.…”
Section: Iav Replication and Hypercytokinemiamentioning
confidence: 99%
“…However, an exaggerated inflammatory response is believed to contribute to H5N1-associated morbidity and mortality [52][53][54][55]. For example, the resistance of pigs to severe H5N1-mediated disease correlated with the lack of a strong pro-inflammatory response following infection [56][57][58]. Combined with evidence that macrophages support productive replication of some IAV strains, excessive cytokine production following H5N1 infection may be a result of productive virus replication in macrophages.…”
Section: Iav Replication and Hypercytokinemiamentioning
confidence: 99%
“…The transmission of HPAIV to mammals is of great concern as it may allow adaptation to mammalian hosts, resulting in acquisition of a pandemic potential for humans. Interestingly, swine, previously thought to act as an important mixing vessel of avian and human influenza viruses, do not seem to play a significant role in the spread of HPAIV H5N1, and natural infections appear to be rare (Choi et al, 2005;Isoda et al, 2006). In this report, we have shown that (i) the viral infectious dose determines the clinical outcome of HPAIV H5N1 infection in cats, (ii) asymptomatic cats shed only minimal amounts of virus and (iii) cats can be effectively protected by vaccination against lethal HPAIV H5N1 challenge infection.…”
Section: Introductionmentioning
confidence: 99%
“…This possibility increases the potential public health threat of H5N1 HPAI. Since its emergence in domestic geese in Guangdong Province, China (6,7), the H5N1 HPAI virus has evolved to form at least 10 distinct phylogenetic clades (8) and has spread to wild migratory waterfowl (9) and to multiple mammalian hosts (10)(11)(12)(13)(14)(15)(16). In April 2005, a massive die-off of wild waterfowl was caused by H5N1 HPAI viruses at Qinghai Lake in China (17,18).…”
mentioning
confidence: 99%